Pengaruh Penambahan Nikel (Ni) Terhadap Sifat Stuktur Kristal Dan Morfologi MOF-5 - Nikmatin Sholichah; Abdul Basith; Rendy Priyasmika (Jurnal Matematika dan Sains (JMS), 2022)
Ni-doped MOF-5s were successfully synthesized by the solvothermal method for 12 hours at 140 °C. The mmol ratio of Ni/Zn was varied, i.e 0,05 and 0,1, to study the effect of Ni(II)-doped on the formation of MOF-5 materials. The Ni-MOF-5 materials were characterized using X-ray diffraction and scanning electron microscopy-energy dispersive X-ray (SEM-EDX). The XRD patterns and morphology of the Ni-MOF-5 were similar to that of synthesized MOF-5 and standard. The results of SEM-EDX showed that nickel was found in the Ni-MOF-5.